2012
DOI: 10.1590/s0100-204x2012000200002
|View full text |Cite
|
Sign up to set email alerts
|

Leaf miner incidence in coffee plants under different drip irrigation regimes and planting densities

Abstract: -The objective of this work was to evaluate the effect of different drip irrigation regimes and planting densities on the incidence of the leaf miner, Leucoptera coffeella, in arabica coffee plants for one year. The experiment was carried out in 2008, in a complete randomized block design, in a split-plot in time arrangement, with four replicates. The treatments consisted of four drip irrigation regimes -soil water balance, irrigations at 20 and 60 kPa soil tensions, and a nonirrigated treatment -, which were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
3
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 15 publications
(10 reference statements)
1
3
0
Order By: Relevance
“…palliative to prevent further damages to the crop, thus corroborating Assis et al (2012) who found greater losses in dryland areas.…”
Section: Resultssupporting
confidence: 70%
“…palliative to prevent further damages to the crop, thus corroborating Assis et al (2012) who found greater losses in dryland areas.…”
Section: Resultssupporting
confidence: 70%
“…Drip irrigation keeps the soil warm and dry between the rows of planted plants, which may harm insect pests that need environments with moderately high humidity and temperatures to reproduce and develop (Rendon and Walton, 2019). Assis et al (2012) found that Drip-irrigated coffee crops have fewer leaf miners than unirrigated ones. However, Daane and Williams (2003) recorded that high volumes of drip irrigation within vines may increase late-season leafhopper populations.…”
Section: Resultsmentioning
confidence: 99%
“…Insecticides treatment through a drip irrigation system can replace or reduce the number of foliar insecticide sprays and represents an alternative method for integrated pest management . However, (Assis et al, 2012) found that drip irrigated coffee crops have fewer leaf miners than un irrigated ones.…”
Section: Introductionmentioning
confidence: 97%
“…These results were also observed by Custódio et al (2009), in a study that identified low infestation of the leafminer during the same period in the south of Minas Gerais state. The South of Minas region presents high levels of rainfall, which leads to unsuitable conditions for the reproduction of the coffee leafminer (ASSIS et al, 2012).…”
mentioning
confidence: 99%